2015
DOI: 10.1111/jzs.12106
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitogenomes of lobsters and crayfish (Crustacea: Decapoda: Astacidea) reveal surprising differences in closely related taxa and convergences to Priapulida

Abstract: We sequenced the complete mitogenomes of three species of Decapoda, Astacidea, comprising Astacida (freshwater crayfish) and Homarida (marine clawed lobsters): 1. Procambarus fallax f. virginalis (Astacida, Astacoidea), 2. Homarus gammarus (Homarida, Nephropoidea) and 3. Enoplometopus occidentalis (Homarida, Enoplometopoidea). Together with the available species in GenBank, the taxon Astacidea is covered with at least one representative for each of the four main subtaxa. Astacidea show unexpectedly diverse gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The Southern hemisphere crayfish (Parastacoidea) and Northern hemisphere crayfish (Astacoidea), both freshwater groups, are well-supported sister taxa as are the reef lobsters (Enoplometopidae) and Nephropidae (the latter family containing the Thaumatochlidae) (Tsang et al 2008;Bracken-Grissom et al 2014). Focusing specifically on the Astacidea, Shen et al (2015) investigated mitochondrial gene order rearrangements and showed convergent evolution in mitochondrial gene order in several instances. This indicates that mitochondrial gene order is not a useful phylogenetic character within this infraorder and will likely be limited in its utility at a deeper phylogenetic level.…”
Section: Phylogeneticsmentioning
confidence: 99%
“…The Southern hemisphere crayfish (Parastacoidea) and Northern hemisphere crayfish (Astacoidea), both freshwater groups, are well-supported sister taxa as are the reef lobsters (Enoplometopidae) and Nephropidae (the latter family containing the Thaumatochlidae) (Tsang et al 2008;Bracken-Grissom et al 2014). Focusing specifically on the Astacidea, Shen et al (2015) investigated mitochondrial gene order rearrangements and showed convergent evolution in mitochondrial gene order in several instances. This indicates that mitochondrial gene order is not a useful phylogenetic character within this infraorder and will likely be limited in its utility at a deeper phylogenetic level.…”
Section: Phylogeneticsmentioning
confidence: 99%
“…The veracity of the current European lobster reference mitogenome in the NCBI database (Accession Number: NC_020020.1) is questioned given its unusual features e.g. missing nad2 , large mitogenome inversion and translocated tRNAs [9, 10, 24] that were not observed in its close relative, the American lobster, Homarus americanus [8]. Although subsequent PCR and Sanger sequencing has been carried out on additional individuals to validate the observed abnormalities [10], a secondary validation by a separate group using different sequencing technology is highly desirable to provide confirmation of this atypical crustacean mitogenome sequence.…”
Section: Discussionmentioning
confidence: 99%
“…missing nad2 , large mitogenome inversion and translocated tRNAs [9, 10, 24] that were not observed in its close relative, the American lobster, Homarus americanus [8]. Although subsequent PCR and Sanger sequencing has been carried out on additional individuals to validate the observed abnormalities [10], a secondary validation by a separate group using different sequencing technology is highly desirable to provide confirmation of this atypical crustacean mitogenome sequence. We, therefore, sequenced another individual of Homarus gammarus using Illumina technology, which removes the need for the laborious and presumably error-prone steps required in traditional mitogenome sequencing such as long-range PCR and primer walking that may lead to the unintentional misassembly of mitogenome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations